2013
DOI: 10.1128/mcb.00280-13
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of Chromatin States Reveals Distinct Mechanisms of Sex-Dependent Gene Regulation in Male and Female Mouse Liver

Abstract: Chromatin state maps were developed to elucidate sex differences in chromatin structure and their impact on sex-differential chromatin accessibility and sex-biased gene expression in mouse liver. Genes in active, inactive, and poised chromatin states exhibited differential responsiveness to ligand-activated nuclear receptors and distinct enrichments for functional gene categories. Sex-biased genes were clustered by chromatin environments and mapped to DNase-hypersensitive sites (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
258
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(283 citation statements)
references
References 84 publications
(131 reference statements)
21
258
3
1
Order By: Relevance
“…Action of these hormones extends at the epigenetic level to DNA methylation and chromatin conformation 16,17 . Analysis of gene expression in different non reproductive tissues indicates the existence of a gender specific influence on transcription 18,19 , which is paralleled at the level of chromatin organization, by specific differences between the sexes 20 . As discussed here below, sex hormone signaling pathways are likely to affect cancer susceptibility through multiple mechanisms, impacting on intrinsic self renewal mechanisms, tumor microenvironment, immune system and metabolism.…”
Section: Introduction (Epidemiology)mentioning
confidence: 99%
“…Action of these hormones extends at the epigenetic level to DNA methylation and chromatin conformation 16,17 . Analysis of gene expression in different non reproductive tissues indicates the existence of a gender specific influence on transcription 18,19 , which is paralleled at the level of chromatin organization, by specific differences between the sexes 20 . As discussed here below, sex hormone signaling pathways are likely to affect cancer susceptibility through multiple mechanisms, impacting on intrinsic self renewal mechanisms, tumor microenvironment, immune system and metabolism.…”
Section: Introduction (Epidemiology)mentioning
confidence: 99%
“…The downstream elements of this sex-bias mechanism are male versus female patterned secretion of GHRH from the hypothalamus into the hypophyseal portal circulation and then corresponding patterned secretion of GH by the pituitary into the general circulation. This finding was discovered by Edén in 1979 (55) and, since then, has been extensively confirmed in mice, rats and humans (27,(45)(46)(47)(48)(49)(50)(56)(57)(58)(59)(60)(61)(62). Circulating GH levels in the male (M) are usually called "pulsatile" (two to four peaks per day) with very low interpulse levels; in the female (F), there is a higher frequency of pulses (seven or more peaks per day) with significant interpulse levels; thus, this is called "more continuous" (Figures 1, 2).…”
Section: A Gap In Knowledge In the Ph Literature Concerning Sex Bias mentioning
confidence: 88%
“…However, it was shown in 1973 by Colby et al (32), and extensively confirmed by numerous studies since then (27,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43), that the feminizing effect on sex-biased liver gene expression of an injection of E2 into a rat or mouse was indirect and had an absolute dependence on the pituitary ( Figure 1). As explained in detail by Waxman and colleagues over the last 2 decades, this neuroendocrine mechanism of sex bias, working through an axis consisting of the hypothalamic arcuate nucleus-growth hormone releasing hormone (GHRH)-growth hormone (GH)-signal transducer and activator of transcription 5 (STAT5) accounts for sex-biased expression of >1,000 genes in the liver and also of body growth and body weight (27,(41)(42)(43)(44)(45)(46)(47)(48) (Figures 2, 3). Parenthetically, STAT5 is the major transcription factor activated by the binding of GH to its receptor on all cell types (27,(41)(42)(43)(44)(45)(46)(47)(48).…”
Section: A Gap In Knowledge In the Ph Literature Concerning Sex Bias mentioning
confidence: 99%
See 2 more Smart Citations